MEMBANGUN SEMANGAT KEWIRAUSAHAAN KUBE MASYARAKAT DESA DI DALAM MEMBANGUN KEMANDIRIAN EKONOMI KELUARGA (STUDI DI DESA TOAPAYA SELATAN KECAMATAN TOAPAYA - Alfiandri, Alfiandri; Edison, Edison; Andrian, Teddy (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2016)
MEMBANGUN SEMANGAT KEWIRAUSAHAAN KUBE MASYARAKATDESA DI DALAM MEMBANGUN KEMANDIRIAN EKONOMI KELUARGA (STUDI DI DESA TOAPAYA SELATAN KECAMATAN TOAPAYA KABUPATEN BINTAN)   Teddy Andrian Alfiandri Edison(edison4086@gmail.com) (Jurusan Ilmu Administrasi Negara FISIP UMRAH)   Abstract: Entrepreneurship is a part adder income that exist within the family environment, one such business that is run by a group of villagers who take advantage of government aid programs such as the program Business Group (KUBE), a group formed by residents / families are less able (disadvantaged) who receive social services through program activities pemerdayaan poor. Where, in such assistance utilized by the villagers to run a business to supplement the family income of the village. The purpose of this study is to develop the spirit of entrepreneurship in the community capital assistance program Business Group (KUBE) in the village of South Toapaya. Informants in this study of 10 people with one person as key informants (key informant). Data analysis techniques used in this research is descriptive qualitative analysis techniques. Results of this research is the village of South Toapaya have a program with business groups namely Business Group (KUBE) but until now businesses are only run by some groups only. The conclusion of this research are the problems that arise in running the program Business Group (KUBE) is because there are only a few groups of people who have the talent and skills in developing programs Business Group (KUBE), so the lack of enthusiastic villagers in running the program. Recomendation in this research is that government aid programs can run well and capable of prospering rural communities in improving the family economy, it is expected that the government, mentor or Business Group (KUBE) can work well together to develop businesses that exist and the government the routine can give directives to socializing to villagers about the efforts made in developing and improving Business Group (KUBE) that they run.